‫ﻓﻌﺎﻟﻴﺔ‬‫ اﻟﺘﺴﻮﻳﻖ‬ ‫اﻟﺸﺒﻜﻲ‬ ‫ﻓﻲ‬ ‫ﺗﻮزﻳﻊ‬ ‫اﻟ‬‫ﻤﻨﺘﺠﺎت‬ ‫دراﺳﺔ‬‫ ﻣﻴﺪاﻧﻴﺔ‬ ‫ﻟﺸﺮﻛﺔ‬ ‫اورﻳﻔﻼم‬ ‫ﺑﻮﻻﻳﺔ‬ ‫ﺳﻮق‬ ‫أﻫﺮاس‬ - زﺑﻴﺪة ‫ﻣﻼﻳﻜﻴ‬‫ﺔ ‬‫‬; ‬‫ﺷﺮﻳﻦ ‫ﻛﺮﻳ‬‫ـ‬‫ﻤﻮ ‬ (My University, 2017)
This study aims to shed light on the problem of network marketing in the distribution of products which is one of the modern methods of marketing. Oriflame is one of the companies that introduced the latter, because the issue of product disposal has become one of the main problems of the majority Productive institutions. In order to address this problem and to confirm the validity of the hypotheses prepared in advance, Oriflame was chosen as an office -Souk Ahras- for the field study as a network marketing and was studied through a questionnaire to collect the necessary data from the study sample.